Pemanfaatan Teknologi Komposter Digital untuk Pengolahan Sampah Organik Rumah Tangga di Desa Kepuharjo Kabupaten Malang - Wincoko, Wincoko; Firman Adi, Anas; Wulan Ndari, Priska (Jurnal Pengabdian Kepada Masyarakat, 2025)
Kepuharjo Village, Karangploso District, Malang, is facing serious problems in household waste management. Initial survey results show that 80% of the waste consists of organic waste, 90% of residents do not separate their waste, and 70% dispose of it directly into the waste disposal site without processing. This condition leads to accumulation, odors, and health risks. The community service activities will be carried out over two months (July–August 2025) involving 10 representatives from non-productive groups. The methods include socialization, training, installation of digital composters, as well as mentoring and evaluation. The results of the community service show that residents are able to operate the digital composters independently. The compost produced has good quality (pH 6.5–8; moisture content 30–40%) and is utilized for plant cultivation. This program reduces the volume of organic waste to the waste transfer station, enhances residents' skills, and opens economic opportunities through compost utilization. The assistance of digital composters has proven effective in increasing the community's capacity to manage organic waste, creating a healthy environment, and empowering non-productive groups towards sustainable economic independence .